Geminin is an indispensable inhibitor of Cdt1 in mouse embryonic stem cells. (14th March 2017) - Hosogane, Masaki; Bosu, Lena; Fukumoto, Emiko; Yamada, Hidetoshi; Sato, Soichiro; Nakayama, Keiko
Abstract : Geminin is implicated in regulation of the cell cycle and differentiation. Although loss of Geminin triggers unscheduled DNA rereplication as a result of interruption of its interaction with Cdt1 in some somatic cancer cells, whether such cell cycle regulation also operates in embryonic stem cells (ESCs) has remained unclear. To characterize the Geminin‐Cdt1 axis in ESCs and compare it with that in somatic cells, we established conditional knockout (KO) of Geminin in mouse ESCs and mouse embryonic fibroblasts (MEFs). Geminin KO ESCs manifest a large flattened morphology, develop polyploidy accompanied by DNA damage and G2 ‐M checkpoint activation, and subsequently undergo apoptosis. Rereplication in Geminin KO ESCs was attenuated by inhibition of G2 ‐M checkpoint signaling or by expression of wild‐type Geminin, but not by expression of a Geminin mutant that does not bind to Cdt1, indicating the importance of sequestration of Cdt1 by Geminin in G2 phase. In contrast, Geminin KO MEFs did not manifest disturbance of the cell cycle unless they were treated to force abnormal accumulation of Cdt1. Together, our results indicate that Geminin is a key inhibitor of Cdt1 in mouse ESCs, but that it plays a backup role in MEFs to compensate for accidental up‐regulation of Cdt1. Abstract : We established conditional knockout of Geminin in mouse ESCs and mouse embryonic fibroblasts. Geminin KO ESCs develop polyploidy accompanied by DNA damage and G2‐M checkpoint activation, but MEFs do manifest disturbance of the cell cycle. Geminin is a key inhibitor of Cdt1 in mouse ESCs, but that it plays a backup role in MEFs to compensate for accidental up‐regulation of Cdt1.